If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3g + 7) = -4(3 + -2g) Reorder the terms: 2(7 + 3g) = -4(3 + -2g) (7 * 2 + 3g * 2) = -4(3 + -2g) (14 + 6g) = -4(3 + -2g) 14 + 6g = (3 * -4 + -2g * -4) 14 + 6g = (-12 + 8g) Solving 14 + 6g = -12 + 8g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8g' to each side of the equation. 14 + 6g + -8g = -12 + 8g + -8g Combine like terms: 6g + -8g = -2g 14 + -2g = -12 + 8g + -8g Combine like terms: 8g + -8g = 0 14 + -2g = -12 + 0 14 + -2g = -12 Add '-14' to each side of the equation. 14 + -14 + -2g = -12 + -14 Combine like terms: 14 + -14 = 0 0 + -2g = -12 + -14 -2g = -12 + -14 Combine like terms: -12 + -14 = -26 -2g = -26 Divide each side by '-2'. g = 13 Simplifying g = 13
| -3y+3x=4 | | 2/5c+4-1/5c_19 | | 2(2x-9)-2x=2(x-2)-7 | | -57+17=-5x+13x | | -10(7+m)=-230 | | 34.5=(2)(3.14)(x) | | 1.1x+1.2x-5.4=-16 | | -7n=-98 | | p^2+p=x | | 59.7=(2)(3.14)(x) | | 8-6a=4(a-3) | | -1.333333+y+y=3 | | 3120=(26000)(0.03)(x) | | 0=12-5x+3y | | ax-r=12 | | 4(6p-8)=24p-23 | | 15r=60 | | 43z-1=4(13z-16) | | -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 |